Solidification of floating dispersed organic droplets and ionic liquid microextraction methods for the determination of non-steroidal anti-inflammatory drugs in human urine - Dyia Syaleyana Md. Shukri, 1989-; Mohd. Marsin Sanagi, supervisor; Wan Aini Wan Ibrahim, supervisor; Fakulti Sains (2013)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2013